Impact of COVID-19 pandemic on the management of paediatric inflammatory bowel disease: An Italian multicentre study on behalf of the SIGENP IBD Group. Issue 3 (March 2021) - Arrigo, Serena; Alvisi, Patrizia; Banzato, Claudia; Bramuzzo, Matteo; Celano, Rosaria; Civitelli, Fortunata; D'Arcangelo, Giulia; Dilillo, Anna; Dipasquale, Valeria; Felici, Enrico; Fuoti, Maurizio; Gatti, Simona; et al.
Abstract: Background: IBD management has been significantly affected during the COVID-19 lockdown with potential clinical issues. Aims: The aim of this study was to analyse the impact of COVID-19 pandemic on the Italian paediatric IBD cohort. Methods: This was a multicentre, retrospective, cohort investigation including 21 different Italian IBD referral centres. An electronic data collection was performed among the participating centres including: clinical characteristics of IBD patients, number of COVID-19 cases and clinical outcomes, disease management during the lockdown and the previous 9 weeks. Results: 2291 children affected by IBD were enrolled. We experienced a significant reduction of the hospital admissions [604/2291 (26.3%) vs 1281/2291 (55.9%); p < 0.001]. More specifically, we observed a reduction of hospitalizations for new diagnosis (from n = 44 to n = 27) and endoscopic re-evaluations (from n = 46 to n = 8) . Hospitalization for relapses and surgical procedures remained substantially unchanged. Biologic infusions did not significantly vary [393/2291 (17.1%) vs 368/2291 (16%); p = 0.3]. Telemedicine services for children with IBD were activated in 52.3% of the centres. In 42/2291(1.8%) children immunosuppressive therapies were adapted due to the concurrent COVID-19 pandemic. Conclusion: Due to the several limitations of the lockdown, cares for children with IBD have been kept to minimal standards, giving priorities to the urgencies and to biologics' infusions and implementing telemedicine services.